Selected economic factors impacting tourist travel in Poland between 2000 and 2012 and a forecast for 2013–2017 - Kućmierz, Paweł Kućmierz; Mazurkiewicz, Łukasz; Walanus, Adam (Geotourism/Geoturystyka, 2014)
The paper presents an analysis of tourist travel in Poland during the 2000–2012 time period and predictions for years 2013–2017. Since 2000 the amount of travelling Polish citizens has declined. Various factors may have impacted this state of matters e.g. the economic crisis or increasing the VAT rate. The biggest decline in tourist travel was observed between 2007 and 2009 and in 2011. On the other hand, the factor which increased the number of visits between 2007 and 2009 may have been the Euro 2012 championship, organized by both Poland and Ukraine. The paper presents a “eurosensitivity” factor, which describes the increase in people visiting selected voivodeships during 2012, primarily due to the Euro 2012 championship. According to the calculations, the voivodeship which benefited from the highest increase was Małopolska. The article also presents an estimation of travel for years 2013–2017.